ADVERBIA DALAM NOVEL ANGKATAN PUJANGGA BARU: NOVEL LAYAR TERKEMBANG KARYA SUTAN TAKDIR ALISJAH-BANA DAN NOVEL BELENGGU KARYA ARMIJN PANE - Susanti, Weni; Agustina, Agustina; Manaf, Ngusman Abdul (Jurnal Bahasa dan Sastra, 2018)
This study was conducted to describe (1) the type of abreviation and (2) the formation of abreviation in the weekly newspaper of Padang Ekspres in January 2018. This research type is qualitative research by using descriptive method. This research data is a kind of abreviation (abbreviations, acronyms, fragments, contractions, and symbols) that exist in the news sentences of the weekly newspaper Padang Ekspres January 2018. The data sources of this research in the newspaper Padang Ekpres Weekly edition in January 2018. Based on the results of data analysis obtained two research findings. First, the type of abreviation in the weekly newspaper Padang Ekspres January 2018, found five types of abreviation, namely (a) abbreviation, (b) acronym, (c)fragments, (d) contractions, and (e) symbols. Second, the formation of abreviation in the weekly newspaper Padang Ekspres January 2018, consists of four processes. (a) The formation of abbreviations consisting of: the first letters of each component; first letters with conjunction, preposition, reduplication, articulation and word; first letters; and first and third letter. (b) The formation of acronyms and contractions consisting of: the first syllabus of each component; first of each component, first two letters of each component, the first three letters of each component, the first two letters of the first two and the first two letters of the second component together with the deletion; and the sequence of various letters and syllables difficult to formulate. (c) The formation of a fragment consist of: that is letters the last syllable of a word and partial splitting sequence. (d) The formation of letter symbol consisting of: that is symbol of letters that characterize size consisting of first letters of consolidation of component, letter symbol expressing data number, and symbol letters that mark currency. Keywords: Adverbs, Novel, Pujangga Baru